2012
DOI: 10.1186/1475-925x-11-50
|View full text |Cite
|
Sign up to set email alerts
|

Identify schizophrenia using resting-state functional connectivity: an exploratory research and analysis

Abstract: BackgroundSchizophrenia is a severe mental illness associated with the symptoms such as hallucination and delusion. The objective of this study was to investigate the abnormal resting-state functional connectivity patterns of schizophrenic patients which could identify furthest patients from healthy controls.MethodsThe whole-brain resting-state fMRI was performed on patients diagnosed with schizophrenia (n = 22) and on age- and gender-matched, healthy control subjects (n = 22). To differentiate schizophrenic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 55 publications
(76 reference statements)
6
37
1
Order By: Relevance
“…Indeed, our classification of patients with child-onset schizophrenia achieved a sensitivity of 90% and specificity of 74%. This finding supports the notion that analysis based on network measures and data mining methods may present a possible strategy for automatic diagnostics for neurological disorders Previous studies on restingstate fMRI achieved similar levels of specificity and accuracy, not only for schizophrenia in adults (Tang et al, 2012;Venkataraman et al, 2012;Shen et al, 2010), but also for other neurological disorders (Welsh et al, 2013;Zeng et al, 2013;Tang et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Indeed, our classification of patients with child-onset schizophrenia achieved a sensitivity of 90% and specificity of 74%. This finding supports the notion that analysis based on network measures and data mining methods may present a possible strategy for automatic diagnostics for neurological disorders Previous studies on restingstate fMRI achieved similar levels of specificity and accuracy, not only for schizophrenia in adults (Tang et al, 2012;Venkataraman et al, 2012;Shen et al, 2010), but also for other neurological disorders (Welsh et al, 2013;Zeng et al, 2013;Tang et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
“…In adult schizophrenic patients previous studies already illustrated the usefulness of non-invasive diagnosis based on the analysis of restingstate fMRI data. Such analysis of brain network properties achieved values for correct classification of up to 94% with 75% accuracy (Tang et al, 2012;Venkataraman et al, 2012;Shen et al, 2010). However, similar analysis of fMRI data from patients with childonset schizophrenia is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on the classification of Schizophrenia patients based http://dx.doi.org/10.1016/j.neunet.2015.04.002 0893-6080/© 2015 Elsevier Ltd. All rights reserved. on fMRI data have been reported with small datasets, achieving good classification accuracies, e.g., Tang et al showed a 93.2% (Tang, Wang, Cao, & Tan, 2012) with 44 matched subjects and Yu et al (2013) experiment with healthy patient siblings achieves 62% accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Preprocessing including realignment and normalization, was performed in the statistical parametric mapping software (SPM8) [14]. Many researchers [3,[17][18][19][20] applied smoothing on the fMRI data, in addition to realignment and normalization preprocessing techniques. In this paper, we focus on the different between a voxel and its neighbors for classification process.…”
Section: Databasementioning
confidence: 99%